222 IMPROVING PREVENTIVE CARE: ASSESSING ADHERENCE TO THE SIXTH AMERICAN COLLEGE OF CHEST PHYSICIANS' RECOMMENDATIONS FOR THROMBOPROPHYLAXIS IN AT-RISK CARDIOVASCULAR AND STROKE PATIENTS IN US HOSPITALS. Issue 1 (1st January 2007) - Amin, A. N.; Stemkowski, S. A.; Lin, J.; Yang, G.
Abstract : Purpose: JCAHO, NQF, and other hospital quality groups promote the adoption of evidence-based prophylaxis regimens to prevent VTE. This study evaluates whether hospitals are providing appropriate thromboprophylaxis to at-risk cardiovascular and stroke patients in accordance with the Sixth American College of Chest Physicians' (ACCP) guidelines. Methods: Premier's Perspective inpatient administrative database was used to assess the VTE prophylaxis rate in acute myocardial infarction (AMI), heart failure (HF), and ischemic stroke patients. Only patients age 40 or older, with a minimum length of stay of 6 days and no contraindications for anticoagulation, were included in the study. Appropriate thromboprophylaxis was determined by comparing the daily use of anticoagulants and compression devices, dosage, and duration of prophylaxis with the ACCP recommendations. Results: A total of 68, 563 hospital discharges (22, 579 AMI, 36, 929 HF, and 9, 055 stroke) from 214 hospitals between January 2002 and September 2005 met the inclusion criteria for the study. VTE prophylaxis rates varied significantly across cardiovascular and stroke diagnostic groups: 49% in ischemic stroke, 43% for AMI, 40% in HF. On average, 42% of all at-risk cardiovascular and stroke patient discharges received ACCP-compliant VTE prophylaxis. Five percent of AMI discharges did not receive any prophylaxis at all compared with 29% of HF and 33% of stroke discharges. In addition, 52% of AMI, 30% of HF, and 18% of stroke discharges did not receive prophylaxis for the recommended duration. Conclusion: VTE prophylaxis for at-risk cardiovascular patients in hospitals is not optimal. The varying reasons for noncompliance in HF and AMI patients suggest differences in practice among specialists that may affect patient outcomes. More effort is required to increase awareness of the ACCP recommendations for thromboprophylaxis for these patients.